Implementasi Proses Sandar Kapal dan Proses Debarkasi Embarkasi Di MV. Kelimutu oleh PT. Pelni Cabang Semarang - Agus Ari Widodo; M Aji Luhur Pambudi; Ridwan (JURNAL TRANSMA, 2025)
Implementation of the ship docking process and debarkation and embarkation is crucial for ensuring the smooth operation of vessels. The ship docking process involves precise positioning at the dock, which requires coordination between the ship's crew and port personnel and modern technology to monitor the position and ensure safety. Meanwhile, the debarkation-embarkation process involves handling passengers and cargo on and off the ship. This study employs a qualitative descriptive method. The sample consists of all components of PT. Pelni Semarang branch related to activities or tasks observed by the researcher during field observations. Data collection techniques include observation, interviews, and documentation. Data analysis techniques involve data reduction, data triangulation, data presentation, and data summarization. This research aims to identify, evaluate, and implement optimization strategies for the ship docking and embarkation-debarkation processes to enhance operational efficiency. Based on interviews and observations, the findings indicate that success can be achieved if the agency involved in managing ship docking and embarkation-debarkation processes can minimize errors or issues that cause operational delays.